(NmATEMATI^ESKOE MODELIROWANIE W SEJSMORAZWEDKE (B/s - (NkORQGIN(B, (NwIKTOR wLADIMIROWI^s; (NsAHAROW(B, (N`RIJ pETROWI^s; (NgLOTOW(B, (No(B.(Nk(B.s; (NtRAPEZNIKOWA(B, (Nn(B.(Na(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 152-155 (79 (NNAZW(B.)s
(NiN(B-(NT GEOLOGII I RAZRAB(B. (NGOR@^IH ISKOPAEMYHs
Keywords: (NmATEMATI^ESKIE ISSLEDOWANIQs; (NsEJSMI^ESKAQ RAZWEDKAs